2014
DOI: 10.1001/jamaophthalmol.2014.2756
|View full text |Cite
|
Sign up to set email alerts
|

Small-Bubble Deep Anterior Lamellar Keratoplasty Technique

Abstract: Stromal disease (ectasia, opacities, scars, or melting) that occurs after penetrating keratoplasty (PK) can variously affect visual outcome. 1,2 To date, even in the presence of healthy endothelium, this type of complication has been treated with subsequent PK. 3 Instead, the selective replacement of the diseased stroma by means of deep anterior lamellar keratoplasty (DALK) using pneumatic dissection (big bubble) has not been attempted, mainly because of the extreme likelihood of breaking the descemetic scar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Anterior lamellar keratoplasty (ALK) was performed using either pneumatic or microkeratome-assisted dissection 10 11. DSAEK and ultrathin DSAEK were also performed in a standardised fashion following the technique described elsewhere 12.…”
Section: Methodsmentioning
confidence: 99%
“…Anterior lamellar keratoplasty (ALK) was performed using either pneumatic or microkeratome-assisted dissection 10 11. DSAEK and ultrathin DSAEK were also performed in a standardised fashion following the technique described elsewhere 12.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the increased CDVA and low number of complications, they later reported that preventing the bubble from expanding into the PK wound was not always possible, requiring conversion to PK. 13,14 When we compare our results to these studies, we also report good visual outcomes, a more controlled corneal dissection and wound construction, and absence of double anterior chamber or conversion to PK events.…”
Section: Discussionmentioning
confidence: 52%
“…10,11 However, there are few reports regarding the use of deep anterior lamellar keratoplasty (DALK) in patients where GF after PK is due to conditions that affect anterior layers of the cornea and spare Descemet's membrane (DM) and endothelium. [12][13][14][15] In light of this, the purpose of our study is to describe a modified DALK technique to rescue failed PK grafts and report its results through a case series of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In previous literature, low success rate to expose DM was observed in some corneal pathology such as scar following bacterial keratitis;[ 15 ] and complications such as DM rupture were likely to occur when performing pneumatic dissection (big-bubble technique) in corneas with extensive scar. [ 24 ] Despite this fact, after corneal stroma is inflated with air and becomes foam-like, it appears that the residual stromal tissue could be dissected easier. Such air-assisted manual DALK was first reported by Balestrazzi et al .…”
Section: Discussionmentioning
confidence: 99%